Riboflavin Attenuates Influenza Virus Through Cytokine-Mediated Effects on the Diversity of the Gut Microbiota in MAIT Cell Deficiency Mice - Li, Ying; Shi, Chun-Wei; Zhang, Yu-Ting; Huang, Hai-Bin; Jiang, Yan-Long; Wang, Jian-Zhong; Cao, Xin; Wang, Nan; Zeng, Yan; Yang, Gui-Lian; Yang, Wen-Tao; Wang, Chun-Feng (Frontiers in Microbiology, 2022)
Influenza is a serious respiratory disease that continues to threaten global health. Mucosa-associated invariant T (MAIT) cells use T-cell receptors (TCRs) that recognize microbial riboflavin derived intermediates presented by the major histocompatibility complex (MHC) class I-like protein MR1. Riboflavin synthesis is broadly conserved, but the roles or mechanisms of riboflavin in MR1–/– mouse influenza infection are not well understood. In our study, immunofluorescence techniques were applied to analyze the number and distribution of viruses in lung tissue. The amount of cytokine expression was assessed by flow cytometry (FCM), ELISA, and qPCR. The changes in the fecal flora of mice were evaluated based on amplicon sequencing of the 16S V3-V4 region. Our study showed that MAIT cell deficiency increased mortality and that riboflavin altered these effects in microbiota-depleted mice. The oral administration of riboflavin inhibited IL-1β, IL-17A, and IL-18 production but significantly increased the expression of IFN-γ, TNF-α, CCL2, CCL3, and CCL4 in a mouse model. The analysis of the mouse flora revealed that riboflavin treatment significantly increased the relative abundance of Akkermansia and Lactobacillus (p < 0.05) and decreased that of Bacteroides. In contrast, MR1–/– mice exhibited a concentrated aggregation of Bacteroides (p < 0.01), which indicated that MAIT cell deficiency reduced the diversity of the bacterial population. Our results define the functions of MAIT cells and riboflavin in resistance to influenza virus and suggest a potential role for riboflavin in enhancing MAIT cell immunity and the intestinal flora diversity. Gut populations can be expanded to enhance host resistance to influenza, and the results indicate novel interactions among viruses, MAIT cells, and the gut microbiota.